The Impact of Differential Parenting: Study Protocol on a Longitudinal Study Investigating Child and Parent Factors on Children’s Psychosocial Health in Hong Kong - Ng, Catalina Sau Man; Chiu, Ming Ming; Zhou, Qing; Heyman, Gail (Frontiers in Psychology, 2020)
Adolescents who believe that their parents treat them differently from their siblings have poorer psychosocial well-being than otherwise. This phenomenon, which is known as parental differential treatment or PDT occurs in up to 65% of families. Past studies have examined socio-demographic variables (e.g., child gender, age, and birth order) as predictors of PDT, but these immutable characteristics do little to inform interventions and help these adolescents. Hence, this study extends past research by investigating links among parent empathy, parent perception of PDT, child perception of PDT, child perception of fairness and child well-being (self-esteem, depression, anxiety, and trust in the relationship with parents). Furthermore, this study tests whether adolescent personality (openness, conscientiousness, extraversion, agreeableness and neuroticism), child empathy, and child perception of fairness moderate these links. This study will utilize a two-wave longitudinal design with a one-year lapse. Data will be collected from 760 Chinese adolescents studying from Secondary One to Secondary Three in 18 schools in Hong Kong and from their parents. We test our theoretical model via a multilevel structural equation model. This study both addresses (a) theoretical debates about relations among empathy, PDT, fairness, and psychosocial well-being and (b) focuses on modifiable factors and behaviors, to inform future interventions, such as parent education.